An Analysis of Teachers’ and Parents’ Perceptions on English Online Learning at Junior High School - Ahmad Subhan Roza; Yeasy Agustina Sari; Wulan Hasanatun Cahya Adi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
Teachers are one of the main factors for the success of education. Parents play an important role in the task and are responsible for the formation of children's character both physically and spiritually. As educators, teachers are the main actors who walk side by side with parents and other important elements. This research analyzes the teachers' perception about English online learning design and the parents' perception about English online learning design at SMP Negeri 01 Seputih Surabaya. This research used a qualitative approach. The results showed that: 1) The teacher's perception of the implementation of online learning in English shows that the teacher feels that online learning is difficult to apply especially in shaping the character of students because teachers are less able to monitor and supervise students directly, lack facilities that support online learning, and teachers also complain that in delivering learning materials, students find it difficult to understand the lessons being taught. 2) Parents' perceptions of the implementation of online English learning show the ineffectiveness of online learning, this is due to parents who feel that their children are not optimal when studying and are still having problems while studying. Keywords: Teachers' Perceptions, Parents'Pperceptions, English Online Learning